Trends and Prospects of Development of Financial Innovations in the Russian Banking Business - O. A. Vasilenko (Мир новой экономики)
The relevance of the article is because the modern development of the Russian banking business takes place in the context of increased competition and crisis phenomena in the financial markets. The policy of constant innovations is one of the main factors for the successful development of banking activity. Financial innovation is a crucial factor in the competitiveness and sustainable development of the banking sector. Of particular relevance is the study of trends, based on which the development of the innovative activity of banks and non-bank credit organisations is currently taking place, as well as the determination of the specifics of the innovation process in the banking sector.The purpose of the article is to conduct research on the current state of the most popular at the present stage financial innovations in the banking sector, identify trends in their development, and determine the future directions for the development of financial innovations in the Russian banking business. In this paper, we analysed analytical information, which allowed us to identify trends in the development of financial innovations in the banking sector, and determine their role in the development of the banking sector in Russia. In the course of the study, the author used the methods of analysis, synthesis, the complexity of the approach, comparison, consistency, and other methods of cognition. Based on the research results and personal experience in the development and implementation of new banking products at Unistream CB, the author predicts the future directions of development of financial innovation in the banking business.The author concludes that their introduction has an influence on the transformation process in the real and financial sectors of the Russian economy, and contributes to the organisation of their effective interaction, accelerates the development of the entire economic system of the country.The main objectives of the development of financial innovations in the banking sector at the present stage are the development and implementation of new banking products. It requires further study of the theoretical and practical aspects of introducing financial innovations, a detailed analysis of domestic and foreign experience, and needs implementation of knowledge gained in practice to modernise and organise productive interaction financial and real sectors of the Russian economy.